ANALISIS PENERAPAN PSAK NO.14 PERSEDIAAN BARANG DAGANG PADA PT.PETRONIKA GRESIK - Rahayu, S.E., M.A., Dwi Inggarwati; Nugraha, Shendi Ferlina (Fakultas Ekonomi Universitas Gresik, 2018)
Inventory is a requirement that must be owned by a company intrading activity. Inventory is the company's current asset needed forcorporate decision-making. The main problems in accounting ofinventories are internal control and the application of PSAK No.14merchandise inventory. The purpose of this research is to know andanalyze about internal control and application of PSAK No.14merchandise inventory at PT. Petronika Gresik. This research is aqualitative research with descriptive method. Data collection techniquesused, namely interviews, observation and documentation. The result ofthis research is PT. Petronika Gresik has implemented a unifiedmanagement system policy and has implemented perpetual logging andweighted average methods as inventory valuation. So it can be concludedthat all accounting activities in PT. Petronika Gresik has been inaccordance with PSAK No. 14 merchandise inventory.ÃƒÆ’Ã†â€™ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â DOI : 10.5281/zenodo.3475668